Are certified firms more prone to eco-product innovation? The moderating role of slack resources. (1st December 2022) - Hernandez-Vivanco, Alfonso; Bernardo, Merce
Abstract: Sustainability is becoming essential for virtually every organization willing to thrive in a globalized world. Nonetheless, the available resources to address the challenges required to switch towards sustainability-oriented firms are scarce and yet necessary to deploy. Thus, this study focuses on the adoption of ISO 9000, ISO 14000 and OHSAS 18001 families of standards as managerial practices that can help firms in promoting eco-product innovation, considering slack resources as a moderator of this relationship. Relying on a sample composed of 2834 firms studied between years 2007 and 2020 and obtained from the Refinitiv® Eikon database, results suggest that firms holding these certifications are more prone to eco-product innovation. More specifically, ISO 14000 acts as the main driver, although its benefits are boosted when implemented in combination with ISO 9000 and/or OHSAS 18001. In fact, firms adopting multiple certifications increasingly use their slack resources to leverage eco-product innovation when firms hold at least intermediate levels of slack. All in all, this is one of the first studies, to the best of the authors' knowledge, analyzing simultaneously the different combinations of these certifications as potential drivers of eco-product innovation, as well as the moderating role of slack resources.